The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1111/cns.12771
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress regulates oxygen‐glucose deprivation‐induced parthanatos in human SH‐SY5Y cells via improvement of intracellular ROS

Abstract: Endoplasmic reticulum stress regulates OGD-induced parthanatos in human SH-SY5Y cells via improvement of intracellular ROS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 40 publications
2
43
0
Order By: Relevance
“…N‐acetylcysteine, a classical antioxidant drug used in chronic obstructive pulmonary disease and contrast‐induced nephropathy, was involved in the metabolism of glutamate, cysteine, and glutathione . NAC was reported to protect cells from oxidative stress, inflammation, and apoptosis in many issues including neuronal cells . In the present study, we demonstrated that NAC treatment could also prevent activation of ER stress via blocking the PI3K/Akt and ERK pathways and consistently ameliorate apoptosis of AVP neurons in acute phase after PEL surgery.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…N‐acetylcysteine, a classical antioxidant drug used in chronic obstructive pulmonary disease and contrast‐induced nephropathy, was involved in the metabolism of glutamate, cysteine, and glutathione . NAC was reported to protect cells from oxidative stress, inflammation, and apoptosis in many issues including neuronal cells . In the present study, we demonstrated that NAC treatment could also prevent activation of ER stress via blocking the PI3K/Akt and ERK pathways and consistently ameliorate apoptosis of AVP neurons in acute phase after PEL surgery.…”
Section: Discussionsupporting
confidence: 61%
“…40 NAC was reported to protect cells from oxidative stress, inflammation, and apoptosis in many issues including neuronal cells. 40,41 In the present study, we demonstrated that NAC treatment could also prevent activation of ER stress via blocking the PI3K/Akt and ERK pathways and consistently ameliorate apoptosis of AVP neurons in acute phase after PEL surgery. However, at the late stage of CDI, NAC treatment did not make a difference in deactivation of ER stress or apoptosis pattern.…”
Section: Therapeutic Target For Er Stress and Apoptosis In CDIsupporting
confidence: 55%
“…In ERS, disorganized disulfide bond formation and disruption may lead to ROS accumulation and oxidative stress [44]. At the same time, ERS can cause mitochondrial damage and increase mitochondrial ROS production [45]. In addition, some UPR components such as CHOP may cause oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant activity is characterized by oxygen‐glucose deprivation (OGD)‐induced injury model of human neuroblastoma SH‐SY5Y cells . Then, in order to evaluate neuroprotective activity of all derivatives, the cytotoxicity was determined by MTT assay to make sure all the compounds were within the testable range and could be tested for subsequent bioactivity.…”
Section: Resultsmentioning
confidence: 99%